An officer and a spy [compact disc, unabridged] : a novel - Harris, Robert, 1957- (Random House Audio, 2013)
Paris in 1895. Alfred Dreyfus, a young Jewish officer, has just been convicted of treason, sentenced to life imprisonment at Devil's Island, and stripped of his rank in front of a baying crowd of twenty-thousand. Among the witnesses to his humiliation is Georges Picquart, the ambitious, intellectual, recently promoted head of the counterespionage agency that "proved" Dreyfus had passed secrets to the Germans. At first, Picquart firmly believes in Dreyfus's guilt. But it is not long after Dreyfus is delivered to his desolate prison that Picquart stumbles on information that leads him to suspect that there is still a spy at large in the French military. As evidence of the most malignant deceit mounts and spirals inexorably toward the uppermost levels of government, Picquart is compelled to question not only the case against Dreyfus but also his most deeply held beliefs about his country, and about himself.